Emerging Factors Implicated in Fibrotic Organ–Associated Thrombosis: The Case of Two Organs - Leiva, Orly; Bekendam, Roelof H.; Garcia, Brenda D.; Thompson, Cristal; Cantor, Alan; Chitalia, Vipul; Ravid, Katya (TH Open, 2019)
Thrombosis is at the heart of cardiovascular complications observed in specific diseases. A heightened thrombosis risk above that in general population in diseases such as myelofibrosis and chronic kidney disease implicates disease-specific mediators of thrombosis. This relative lack of information regarding the mechanisms of thrombosis in specific organ pathologies hitherto has remained limited. Evolving literature implicates some soluble factors in the blood of patients with discrete disorders, inflicting fundamental changes in the components of thrombosis. In this era of precision medicine, integrating these disease-specific factors in a comprehensive thrombotic risk assessment of patients is imperative in guiding therapeutic decisions. A complex network of mechanisms regulates each organ pathology and resultant thrombotic phenotypes. This review surveys different effectors of thrombogenicity associated with two pathologically fibrotic organs used as model systems, the bone marrow and kidney, as well as focuses attention to a common inducer of fibrosis and thrombosis, lysyl oxidase.
Keywords: thrombosis; myelofibrosis; chronic kidney disease; lysyl oxidase; fibrosis